The sanctuary - Khoury, Raymond (Dutton, 2007)
More than 250 years after a pretender marquis escapes the palazzo of his vengeful prince, an American Army unit discovers a secret lab in Baghdad where victims have been subjected to torturous experiments, a finding that places two women on the trail of an ancient mystery.